Technological capabilities and competitive advantages, bibliometric analysis - Estévez-Torres, Ailen (2024)
The research focuses on a systematic review of the scientific production on “Technological Capabilities as Competitive Advantages”. It uses a methodology based on a bibliometric study of international databases such as Scielo, Redalyc, Dialnet and DOAJ. The results reveal that this area is relatively young but growing in importance. It is noteworthy that most of the researchers come from Mexico and Spain, reflecting a particular interest in these regions. Seven different approaches are identified, demonstrating diversity in research perspectives, and tools such as VOSviewer and Excel are used for rigorous and scientific analysis.